2007
DOI: 10.1161/strokeaha.106.477448
|View full text |Cite
|
Sign up to set email alerts
|

Recovery of Cognitive Function After Surgery for Aneurysmal Subarachnoid Hemorrhage

Abstract: Background and Purpose-Abnormalities in neurocognitive function are common after surgery for aneurysmal subarachnoid hemorrhage, even among patients with good functional outcomes. The time course of neurocognitive recovery, along with the long-term effects of mild intraoperative hypothermia (33°C) and aneurysm location, is unknown. We determined these in a subset of subarachnoid hemorrhage patients enrolled in the Intraoperative Hypothermia for Aneurysm Surgery Trial (IHAST). Methods-We performed a longitudina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
47
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(48 citation statements)
references
References 29 publications
0
47
0
1
Order By: Relevance
“…Human SAH results in a wide range of sustained cognitive dysfunction [1,2,25]. Visual and spatial memory is commonly affected.…”
Section: Discussionmentioning
confidence: 99%
“…Human SAH results in a wide range of sustained cognitive dysfunction [1,2,25]. Visual and spatial memory is commonly affected.…”
Section: Discussionmentioning
confidence: 99%
“…26 Abnormalities in cognitive function are common after surgery for aneurysmal SAH, even among patients with a good functional outcome, and can occur in up to 44% of survivors. [27][28][29] This academically funded study was done without any industry support using generic medications and weakness would include lack of on-site trial monitoring due to restraints in funding. We have not incorporated daily blood pressure data in the trial design.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies using diverse designs have consistently demonstrated that intellectual impairment is very prevalent after aSAH. Although cognitive function tends to improve over the first year, 64 global cognitive impairment is still present in Ϸ20% of aSAH patients and is associated with poorer functional recovery and lower quality of life. 65 Cognitive deficits and functional decline are often compounded by mood disorders (anxiety, depression), fatigue, and sleep disturbances.…”
Section: Natural History and Outcome Of Asahmentioning
confidence: 99%